2008
DOI: 10.1111/j.1708-8208.2007.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Bone Tissue Responses to Turned and Oxidized Implants in the Rabbit Tibia

Abstract: The present study confirms the idea that implant surface modification alters the bone tissue response to titanium. The early bone formation following surgery occurs directly on the moderately rough oxidized surface, while turned titanium surfaces are integrated by the ingrowth of bone from the adjacent bone marrow and preexisting bone tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 20 publications
2
54
0
1
Order By: Relevance
“…Clinical studies have shown that the IML protocol is a suitable alternative to conventional two-stage implants based on the prevalence of post-operative negative clinical outcomes such as osseointegration failure, implant mobility, pain and discomfort. 1,2 Similar findings were found in animal experiments [3][4][5][6] and human histological studies. 7,8 A systematic review of clinical studies concluded that it is possible to successfully load dental implants immediately or soon after their placement in selected patients, although failure rates tend to be greater when compared with conventional loaded implants.…”
Section: Introductionsupporting
confidence: 78%
“…Clinical studies have shown that the IML protocol is a suitable alternative to conventional two-stage implants based on the prevalence of post-operative negative clinical outcomes such as osseointegration failure, implant mobility, pain and discomfort. 1,2 Similar findings were found in animal experiments [3][4][5][6] and human histological studies. 7,8 A systematic review of clinical studies concluded that it is possible to successfully load dental implants immediately or soon after their placement in selected patients, although failure rates tend to be greater when compared with conventional loaded implants.…”
Section: Introductionsupporting
confidence: 78%
“…From the mid-1990s to date, it has been experimentally demonstrated that osseointegration is improved and accelerated through various roughening procedures [67,68], such as sand blasting [69][70][71], acid etching [72][73][74], anodic oxidation [75][76][77], and even laser etching [67,68,[78][79][80], and that there exists an optimal range in the micrometer scale [81]. The so-called moderately microroughened implant surfaces have been proven to present improved osseointegration in experimental and in clinical studies [82,83].…”
mentioning
confidence: 99%
“…The percentages of bone-to-implant contact and the bone density of the anodized implants were observed to be 57.03±21.86 % and 40.86±22.73 %, whereas the machined implants were 37.39±23.33 % and 3.52±4.87 %, respectively. Burgos et al 34 Despite titanium's biological compatibility, it is considered to be an inorganic material. This means that the metal does not form part of the human body.…”
Section: Anodizingmentioning
confidence: 99%